2014
DOI: 10.1007/s00428-014-1599-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutational status of KRAS, NRAS, and BRAF in primary clear cell ovarian carcinoma

Abstract: Ovarian clear cell carcinoma (OCCC) is a subtype of epithelial ovarian cancer with characteristic biological features and aggressive clinical behavior. OCCCs show a pattern of gene mutations different from other type I ovarian malignancies, notably a higher frequency of PIK3CA mutations. In low grade serous ovarian cancer, KRAS and BRAF mutations are frequent, but little data are available on the mutational status of these genes in OCCCs. To clarify this issue, we designed a clinicopathological study with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 50 publications
5
23
0
Order By: Relevance
“…The present study confirms the absence of BRAF mutations, underling once again that BRAF alterations are a very rare event and that the PI3K/AKT pathway is the principal pathway for carcinogenesis and progression, for this kind of ovarian tumour 19. This is in line with the data presented by Singer et al and Dodds et al 9 39.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study confirms the absence of BRAF mutations, underling once again that BRAF alterations are a very rare event and that the PI3K/AKT pathway is the principal pathway for carcinogenesis and progression, for this kind of ovarian tumour 19. This is in line with the data presented by Singer et al and Dodds et al 9 39.…”
Section: Discussionsupporting
confidence: 93%
“…Few and contrasting data have been reported, until now, regarding mutational status of KRAS . We found a lower percentage of KRAS hotspot mutations (8/63; 13%) in 63 patients with OCCC compared with PI3KCA hotspot mutations (20/63; 32%), but in line with our previous study 19. Our percentage of KRAS hotspot mutations in OCCC is higher than that of 4.7% found by Jones et al in their study, but in line with that showed in a recent study of 69 patients with OCCC analysed by next generation sequencing, where KRAS was found altered in 11% of cases 16 36.…”
Section: Discussionsupporting
confidence: 92%
“…KRAS mutation is 0% to 5% in non-endometrioid endometrial cancers. [46][47][48][49][50][51][52][53][54][55][56] The frequency of KRAS mutations in cervical cancer ranges between 5% and 14%. In the United States, the frequency of KRAS mutation is 8.8% in patients with cervical cancer.…”
Section: Frequency Of Ras Mutation In Genitourinary Cancermentioning
confidence: 99%
“…The variant pattern revealed a heterogeneous mutational landscape, but is largely in line with what has previously been reported. The oncogene KRAS is often mutated in low proliferating, type 1 ovarian tumors (23). A single KRAS variant was found in our cohort, in line with the previously reported overall variant frequency of 7–14% in OCCC (21, 23).…”
Section: Discussionmentioning
confidence: 99%